Effect of variation concentrations of cajuput oil and magnets on engine performance and flue gas emissions - Perdana, Dony; Said, Nur; Mamat, Rizalman (Konversi, 2024)
This studies proposes the effect of variations concentration of cajupuut oil and magnetic field of attraction on internal combustion engine performance and flue gas emissions. The increasing demand for petroleum energy is increasing, in line with the rising levels of flue gas emissions produced using transportation and the industrial world. Therefore, environmentally friendly alternative fuels are needed. Because the availability of fossil fuels cannot be renewed and their existence is increasingly depleting. This problems can overcome by saving fuels consumption. One way to save fuels are by adding bio-additives from cajupuut oil and a magnetic field to the fuel line. This research uses a direct test method using tools like a chassis dynamometer and gas analyzer. Pertalite fuel is mixed with various concentrations of cajupuut oil, six cc, eight cc, and ten cc and with addition of a magnetic fields strength of 10,000 Gauss of the genio motorcycle fuel line. This research has found that influence of variation of concentration in cajupuut oil and the magnetic field of attraction significantly impact engine performance and flue gas emissions. A mixture of eucalyptus ten ml with a magnetic field of attraction produces the highest maximum power and torque of 8.35 Hp and 11.77 Nm, respectively. Meanwhile, CO emissions have a level of 0.1%, but the highest CO2 level is 9.6% compared to other concentrations.